Somatic instability of CTG repeats in the cerebellum of myotonic dystrophy type 1. Issue 1 (29th April 2013) - Jinnai, Kenji; Mitani, Maki; Futamura, Naonobu; Kawamoto, Kunihiko; Funakawa, Itaru; Itoh, Kyoko
<x xml:space="preserve">Abstract</x> Introduction: We statistically analyzed somatic instability of the CTG expansion in the central nervous system and visceral organs in 7 patients with myotonic dystrophy type 1 and also report intracerebellar instability in 2 patients. Methods: CTG repeat expansion was estimated in the samples from autopsied brains and visceral organs by Southern blot analysis. Pathological study was performed. Samples were taken from several sites in the cerebellum to examine intracerebellar instability. Results: The CTG repeat expansion was shortest in the cerebellar cortex among all tissues examined. With regard to the intracerebellar difference, the shortest expansion was seen in the cortices of the hemisphere and vermis, whereas it was moderate in the dentate nucleus and longest in the white matter of the hemisphere and middle cerebellar peduncle. Conclusions: The shortest expansion might be attributable to packed granule cells in the cerebellar cortex. Further analysis of cell‐specific methylation states might elucidate the enigma of somatic instability. Muscle Nerve, 2013